Short-term and mid-term effects of thoracoscopic repair of esophageal atresia: No anastomotic leaks or conversions to open technique - Galazka, Przemyslaw; Skinder, Dominika; Styczynski, Jan (Frontiers in Surgery, 2022)
The frequency rate of esophageal anastomosis leaks after thoracoscopic correction of esophageal atresia (EA) in the current literature is reported as 5.6-24.7% and conversion rate 2-53%. The objective of this retrospective study was the characteristics of EA and analysis of the safety and efficacy of EA repair with the use of thoracoscopic approach in the single academic center, as well as risk factors analysis in the context of short-term and mid-term follow-up status. Retrospective analysis of management of all consecutive newborns affected by EA hospitalized in our department over a period between 2013-2022, including pre-operative, peri-operative and post-operative management, together with outcome, complications and long-term follow-up status was performed. Total 38 patients with median birth weight 2570 g (range; 1020-3880) were treated over the study period, including 30/38 (78.9%) with additional congenital anomalies. Overall, 30 patients underwent primary anastomosis of the esophagus and 8 underwent multi-staged procedure, with or without an initial ligation of tracheo-esophageal fistula and delayed primary anastomosis. Overall survival for all patients was 0.894±0.050, with median follow-up 4.5 years. We noted neither anastomotic leaks nor conversions to open technique in our cohort. Implementation of vancomycin prophylaxis was successful in preventing post-operative central venous access related infectious complications. At the end of follow-up, 85% of patients has Lansky performance score ≥80. Risk factors analysis for length of hospitalization, overall survival, Lansky performance status, and neurological impairment were analyzed. In conclusion, we have found that outcome of thoracoscopic repair of EA in terms of surgery-dependent morbidity (anastomosis leakage, conversion rate to open surgery), provides benefit to those previously reported in the literature, regardless of the prognostic criteria of classification system.